2003
DOI: 10.1096/fj.02-0560fje
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐8 secreted by endothelial cells induces Chemotaxis of melanoma cells through the chemokine receptor CXCR1

Abstract: There is increasing evidence that both cell adhesion molecules and soluble factors are involved in tumor metastasis. We have found that endothelial cells secrete chemoattractants that can induce melanoma cell chemotaxis. Protein separation on an ion-exchange column shows the association of IL-8 with fractions that contain the chemoattractant activity. This activity is completely lost from the conditioned medium after immunoprecipitation with anti-IL-8 antibodies, indicating that IL-8 is the major melanoma chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 54 publications
4
44
1
Order By: Relevance
“…It was shown that the migration of CXCR1-and CXCR2-expressing endothelial cells is predominantly mediated through CXCR2 (Addison et al, 2000;Loukinova et al, 2000; Heidemann et al, 2003). On the other hand, a recent report suggests that in melanoma cells, CXCL-8-mediated chemotaxis is mainly mediated through CXCR1 (Ramjeesingh et al, 2003). We, however, did not observe any significant differences in CXCL-8-dependent motility and invasion between CXCR1-or CXCR2-overexpressing cells.…”
Section: Discussioncontrasting
confidence: 77%
“…It was shown that the migration of CXCR1-and CXCR2-expressing endothelial cells is predominantly mediated through CXCR2 (Addison et al, 2000;Loukinova et al, 2000; Heidemann et al, 2003). On the other hand, a recent report suggests that in melanoma cells, CXCL-8-mediated chemotaxis is mainly mediated through CXCR1 (Ramjeesingh et al, 2003). We, however, did not observe any significant differences in CXCL-8-dependent motility and invasion between CXCR1-or CXCR2-overexpressing cells.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies have shown that the angiogenic effects of IL-8 in human microvascular endothelial cells and NSCLC were mediated by CXCR2 (Addison et al, 2000;Salcedo et al, 2000;Heidemann et al, 2003). The chemotactic response of melanoma cells to IL-8 was mediated by CXCR1 (Ramjeesingh et al, 2003), and the mitogenic activity of IL-8 was mediated by both CXCR1 and CXCR2 in colon cancer (Li et al, 2001), but only by CXCR1 in monocytes (Browning et al, 2000). Our results show that CXCR1 is the major receptor that mediates the mitogenic function of IL-8 in lung cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Both receptors are G protein-coupled seventransmembrane domain receptors, but different biological functions may be mediated by the different receptors. CXCR1 is believed to mediate the chemotactic activity, whereas CXCR2 mediates the angiogenic activity of CXC ELR þ chemokines such as IL-8 (Heidemann et al, 2003;Ramjeesingh et al, 2003;Bates et al, 2004).…”
Section: Discussionmentioning
confidence: 99%